2010
DOI: 10.1002/cjce.20340
|View full text |Cite
|
Sign up to set email alerts
|

Co‐current descending two‐phase flows in inclined packed beds: Experiments versus simulations

Abstract: The effect of inclination angle of a packed bed on its corresponding gas-liquid flow segregation and liquid saturation spatial distribution was measured in co-current descending gas-liquid flows for varying inclinations and fluid velocities, and simulated using a two-phase Eulerian computational fluid dynamics framework (CFD) adapted from trickle-bed vertical configuration and based on the porous media concept. The model predictions were validated with our own experimental data obtained using electrical capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…Atta et al [3] and Schubert et al [4] were the first to describe experimentally and numerically the hydrodynamics of inclined trickle beds. Their studies demonstrated the strong correlation between phase segregation in gas-liquid descending flows and vessel tilt angle.…”
Section: Introductionmentioning
confidence: 99%
“…Atta et al [3] and Schubert et al [4] were the first to describe experimentally and numerically the hydrodynamics of inclined trickle beds. Their studies demonstrated the strong correlation between phase segregation in gas-liquid descending flows and vessel tilt angle.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pulse flow regime properties such as pulse frequency and propagation velocity were found to decrease as compared to conventional vertical trickle beds. Atta et al (2010) conducted, in parallel to Schubert et al (2010a) experimental work, numerical simulations to identify the main causes for stratification in tilted trickle beds. Among the several drag force closures in trickle beds (Wang et al, 2013), use was made of the relative permeability model within an Eulerian computational fluid dynamics framework to capture the physics of local flow and liquid holdup distribution inside the slanted trickle beds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a great deal of efforts is being directed towards the design of suitable distributors and/or selection of appropriate packings and internals to minimize fluid maldistribution during ship motion (Armstrong et al, 2000;Darredeau, 2001;Duss and Roza, 2014;Fraysse and Werlen, 2002;Haroun et al, 2013;Kalbassi and Zone, 2005). Other research groups have chosen to study the hydrodynamics prevailing inside stationary inclined packed bedsconjectured to be limiting column postures on a ship - (Atta et al, 2010;Bouteldja et al, 2013;Schubert et al, 2010a) or when packed columns are subjected to slow axial vessel rotations (Bieberle et al, 2013;Härting et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such simulations need to be validated before they can be used to design industrial systems with confidence (Dudukovic, 2010). Tomographic imaging techniques can provide the validation studies required for these CFD models (Atta, Hamidipour, Roy, Nigam, & Larachi, 2010;Atta, Schubert, Nigam, Roy, & Larachi, 2010b;Bazmi, Hashemabadi, & Bayat, 2012;Boyer, Koudil, Chen, & Dudukovic, 2005;Gunjal, Kashid, Ranade, & Chaudhari, 2005;Hamidipour, Chen, & Larachi, 2013;Krepper, Reddy Vanga, Zaruba, Prasser, & Lopez de Bertodano, 2007;Lopes & Quinta-Ferreira, 2010;Lopes, Quinta-ferreira, & Larachi, 2012;Rabha et al, 2013b;Robbins, El-bachir, Gladden, Cant, & von Harbou, 2012). In one of these studies, summarized in Figure 18.10, an EulereEuler computational model was compared with wire mesh sensor measurements of the time-averaged voidage in the bubble column (Krepper et al, 2007).…”
Section: Future Trendsmentioning
confidence: 99%